Morphological characteristics of blood cells in monitor lizards: is erythrocyte size linked to actual body size? - Frýdlová, Petra; Hnízdo, Jan; Chylíková, Lenka; Simková, Olga; Cikánová, Veronika; Velenský, Petr; Frynta, Daniel (Integrative zoology, 2013)
Blood cell morphology and count are not uniform across species. Recently, between-species comparisons revealed that the size of red blood cells is associated with body size in some lizard taxa, and this finding was interpreted in the context of the metabolic theory. In the present study, we examined the numbers and the size of blood cells in 2 species of monitor lizards, the mangrove-dwelling monitor (Varanus indicus) and the savannah monitor (V. exanthematicus), and we compared these traits in individuals of different body size. The results revealed that during the course of ontogeny, the size of red blood cells increases with body mass. Because the mass-specific metabolic rate decreases with body size and the cell volume-to-surface ratio decreases with the cell size, changes in the erythrocyte size might be the result of oxygen transport adjustment.
Keywords: druhová specificita; Male; Basal Metabolism; bazální metabolismus; velikost buňky; mužské pohlaví; Species Specificity; krevní buňky; Lizards; Blood Cells; leukocyty; spotřeba kyslíku; ještěři; Oxygen Consumption; Animals; ženské pohlaví; Body Size; zvířata; Leukocytes; erytrocyty; velikost těla; Erythrocytes; Female; Cell Size